REAL and SCOPE: Evolution from Simulation Team Training to Leadership Curriculum Development for Residents and Fellows - Waters, Peter M.; Peter Weinstock (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Postgraduate medical training and post-training career continuing medical education in surgical subspecialty fields focus predominately on developing and mastering technical expertise and voluminous educational content, all of which are important and necessary. However, there is limited organized learning on leadership and non-technical skills (situational awareness, teamwork, communication, task management, decision-making) for surgeons in training, and thereafter as attending faculty, to gain expertise in leading the OR team of surgeons, anesthesiologists, and nurses during complex surgery. Aside from our simulation work on technical skills, we started and grew our training in team skills, leadership, and followership over the past decade-plus. We advanced to not only in-person professional assessments of simulated performances of case scenarios but also the use of audiovisual review with validated scoring (NOTSS, ANTS, SPLINTS). This led to use of these tools in assessing live OR performance (REAL) and coaching (SCOPE) with educational debriefings for the betterment of the individual and the team of professionals. Now, we have a formal curriculum for orthopaedic surgery residents during their third year of training and pediatric surgical fellows (orthopaedic surgery, otolaryngology, plastic surgery, sports medicine, and urology) throughout their fellowship year. We use simulation, REAL, and SCOPE amongst other technics, with formative and summative assessments, to improve their leadership, non-technical skills, and emotional intelligence. Over the past 5 years, the leadership curriculum for surgical fellows and now residents has been highly successful. Our orthopaedic surgery residents and pediatric orthopaedic surgery and sports medicine fellows are better equipped to handle conflict, foster within and across profession collaboration, work in diverse environments, and build and lead a team both on a daily basis and over time. This increases patient safety, mitigates risk, and leads to better outcomes. We encourage others to use these or similar tools in their institutions and programs